Perceptions on the use of recycled water for produce irrigation and household tasks: A comparison between Israeli and Palestinian consumers. (1st November 2021) - Craddock, Hillary A.; Rjoub, Younes; Jones, Kristal; Lipchin, Clive; Sapkota, Amy R.
Abstract: Water scarcity has resulted in extensive wastewater recycling for agricultural irrigation in both Israel and the Palestinian Territories. However, minimal data have been collected regarding perceptions about wastewater recycling between the populations in these two areas. While geographically close and economically linked, these two populations differ in terms of governance, income, and access to technology for wastewater recycling. To address the data gap pertaining to perceptions of wastewater recycling, a survey was administered among a convenience sample of subjects (n = 236) recruited from Eilat, Israel and Bethlehem, West Bank, from May to November 2018. The survey included questions addressing knowledge of water sources, water scarcity, and recycled water; willingness to use recycled water for produce irrigation and household tasks; and demographics. Israeli willingness to use recycled water for various purposes ranged from 8.3% to 55.1%, and more than half of Israeli respondents were willing to serve both raw and cooked produce irrigated with recycled water. Willingness to use recycled water ranged from 28.9% to 41.7% among the Palestinian respondents, and Palestinian respondents were more willing to engage in high-contact uses (i.e. drinking and cooking) than Israeli respondents. Among the Israeli respondents, experience or familiarity with wastewater recycling and water contamination were frequently significantly associated with willingness to use recycled water. In contrast, among Palestinian respondents, personal water contamination experience, home water safety testing, and trust in authorities to monitor recycled wastewater reuse were frequently significantly associated with willingness to use recycled water. Given the likely increasing water stress in both Israel and the Palestinian Territories, as well as the continued evolution of wastewater treatment technologies and the substantial amount of agricultural trade ongoing between Israel and the Palestinian Territories, it is important to identify effective and appropriate outreach and communication strategies to enable successful and acceptable water recycling. Graphical abstract: Image 1 Highlights: Israeli willingness to use recycled water for various purposes ranged from 8.3 to 55.1%. Willingness ranged from 28.9 to 41.7% among the Palestinian respondents. Palestinian respondents were more willing to engage in high-contact uses. Willingness was frequently associated with water contamination experience. Stakeholder concerns and willingness differ among populations & must be understood.